Unit-load storage assignment strategy for warehouses in seismic areas. (September 2015) - Bortolini, Marco; Botti, Lucia; Cascini, Alessandro; Gamberi, Mauro; Mora, Cristina; Pilati, Francesco
Highlights: Optimisation of unit-load storage systems located in seismic areas. Discussion of an effective assignment strategy for unit-load warehouses. Joint analysis of the storage/retrieval travel time and the rack stability. Multi-scenario case study taken from the beverage sector for an Italian company. Effective load configurations prevent seismic risks with high logistic performances. Abstract: The reports from the strong earthquakes that hit seismic regions, as Italy, frequently show the damages occurring to the storage systems and the collapse of their racks, with devastating social and economic consequences. The loads stored in such systems represent the most of their weight, so that the overall structure stability is expected to highly depend on the chosen storage assignment policy. Conventional approaches relate the load assignment to the storage/retrieval (S/R) travel time, affecting the handling costs, neglecting any further issue. This paper faces the so-called unit-load assignment problem (ULAP) for industrial warehouses located in seismic areas presenting an innovative integer linear programming (ILP) model. The model includes both the S/R travel time and an innovative stability condition for the rack collapse prevention during seismic events. A case study, based on a multi-scenario analysis, is discussed to show the benefits coming from the application of the proposed strategy and to assess the impact of the stability issues on the average single-command travel time. The key results outline the effectiveness of the proposed strategy revealing that significant improvements in the structure stability are achievable with little decrease of the S/R efficiency.